2015
DOI: 10.1016/j.jevs.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Evaluations of Sulpiride After Intravenous, Intramuscular, and Oral Single-Dose Administration in Jennies (Equus asinus)

Abstract: a b s t r a c tSulpiride is an antipsychotic human drug. It is commonly used to encourage ovulation in noncycling mares and to stimulate lactation in adoptive mares. No pharmacokinetic data are available for donkeys. The aim of this study was to assess the pharmacokinetics profile of sulpiride after intravenous (IV), intramuscular (IM), and oral (PO) administrations in healthy jennies. Animals (n ¼ 6) were treated with sulpiride, 1 mg/kg by IV, IM, and PO routes according to a randomized cross-over design (3 Â… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 23 publications
7
10
1
Order By: Relevance
“…However, although interspecies allometric scaling needs further refinements and has limitations, it is still a potential tool and rational option for the estimate of pharmacokinetic parameters in species for which there are few data available (Huang & Riviere, ). The V ss of LSP in the current study was small, in agreement with those reported for sulpiride in the donkey and horse (Giorgi et al, , ). The V ss for LSP calculated in pharmacokinetic study in humans after IV administration (Xu et al, ) is higher than that in the present study but still moderate (1,300 ml/kg).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, although interspecies allometric scaling needs further refinements and has limitations, it is still a potential tool and rational option for the estimate of pharmacokinetic parameters in species for which there are few data available (Huang & Riviere, ). The V ss of LSP in the current study was small, in agreement with those reported for sulpiride in the donkey and horse (Giorgi et al, , ). The V ss for LSP calculated in pharmacokinetic study in humans after IV administration (Xu et al, ) is higher than that in the present study but still moderate (1,300 ml/kg).…”
Section: Discussionsupporting
confidence: 93%
“…The lack of adverse effects in goats concurs with a previous studies in nurse mares and jennies (Giorgi et al, , ) and with the good tolerance previously reported in human subjects (Mauri, Bravin, Bitetto, Rudelli, & Invernizzi, ). This is also in‐line with clinical reports showing an excellent safety profile of sulpiride after 2 mg/kg once a day for a 3‐week treatment period (Panzani et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations